Representações sociais de saúde nos Akwẽ/Xerente e as relações entre os sistemas de atenção à saúde indígena - Marquezan, Rogério Ferreira (Universidade Federal do Tocantins, 2019)
This thesis seeks to describe elements of Akwẽ/Xerente social representations and to analyze their implications for health care systems. Based on the theoretical premise that all societies culturally organize their conception of health, how to provide care when they become ill, and the roles related to care, I approach both the biomedical system and the traditional Xerente system as cultural systems of health care. The Akwẽ /Xerente are part of the Macro-jê linguistic trunk and currently inhabit the right bank of the Tocantins river. Throughout the historical process of colonization these people have been adapting to the contact with non-Indians, experiencing a significant population growth in the last decades. Indigenous policies in Brazil have undergone a significant change with the creation of the National Policy of Attention to Indigenous Peoples in 1999, which now provides for the organization of differentiated health care through the implementation of the Indigenous Special Sanitary Districts responsible for the execution, planning, training, social control and the integration between traditional practices and the biomedical model. Over the years the effectiveness of this model of differentiated attention was discussed. We traced the methodological path of ethnography and documentary analysis to produce excerpts about the main aspects that emerged in the relationship between the Xerente and the biomedical care system. The results indicate that factors such as food, access to medicines, relationships with cosmology beings and involvement in local and external political instances have a direct implication in the relationship between Xerente and biomedical health care systems. It is also verified that the characteristics related to the Xerente factionalism have great importance in their social constitution as well as in relation to the organization of an indigenous policy that contemplates the whole community. From the results, we discuss the implications for the systems of attention under the perspective of professional training, social control and the possibilities of constructing effectively dialogical spaces in the field of indigenous health.